2017
DOI: 10.18203/2320-6012.ijrms20173958
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of adolescent pregnancy complications in a rural area of South India

Abstract: Background: Adolescent pregnancy is dangerous for the mother, child and the community and teenage girls are twice as likely to die of pregnancy and childbirth related complications as opposed to older women. Aim was to know the complications of adolescent pregnancies. And to study the socio-demographic profile of adolescent pregnancies.Methods: A total of 144 adolescent pregnant women, aged between 15-19 years were selected for the prospective study. Information on their socio-demographic variables and pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Adolescent pregnancy is the leading cause of adolescent maternal morbidity and mortality globally (3). Moreover, stillbirths are also prevalent among young adolescents in India (4), A high percentage of pregnant adolescents face complications like low birth weight (LBW), cesarean-section, and preterm deliveries (5). Our research group is working in the field of STI diagnostics for the past several years and observed that infections caused by Chlamydia trachomatis (CT) (6)(7)(8)(9), Neisseria gonorrhoeae (NG) (9)(10)(11)(12)(13)(14), and Trichomonas vaginalis (TV) (15)(16)(17) are most common sexually transmitted infections (STIs) with prevalence in the range of 7-29, 5-19 and 2-14% respectively, in symptomatic adult women (18).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent pregnancy is the leading cause of adolescent maternal morbidity and mortality globally (3). Moreover, stillbirths are also prevalent among young adolescents in India (4), A high percentage of pregnant adolescents face complications like low birth weight (LBW), cesarean-section, and preterm deliveries (5). Our research group is working in the field of STI diagnostics for the past several years and observed that infections caused by Chlamydia trachomatis (CT) (6)(7)(8)(9), Neisseria gonorrhoeae (NG) (9)(10)(11)(12)(13)(14), and Trichomonas vaginalis (TV) (15)(16)(17) are most common sexually transmitted infections (STIs) with prevalence in the range of 7-29, 5-19 and 2-14% respectively, in symptomatic adult women (18).…”
Section: Introductionmentioning
confidence: 99%